Comparison between Tibetan and Small-tailed Han sheep in adipocyte phenotype, lipid metabolism and energy homoeostasis regulation of adipose tissues when consuming diets of different energy levels. Issue 7 (14th October 2020) - Jing, Xiaoping; Zhou, Jianwei; Degen, Allan; Wang, Wenji; Guo, Yamin; Kang, Jingpeng; Liu, Peipei; Ding, Luming; Shang, Zhanhuan; Qiu, Qiang; Ding, Xuezhi; Long, Ruijun
Abstract: This study aimed to gain insight into how adipose tissue of Tibetan sheep regulates energy homoeostasis to cope with low energy intake under the harsh environment of the Qinghai-Tibetan Plateau (QTP). We compared Tibetan and Small-tailed Han sheep ( n 24 of each breed), all wethers and 1·5 years of age, which were each divided randomly into four groups and offered diets of different digestible energy (DE) densities: 8·21, 9·33, 10·45 and 11·57 MJ DE/kg DM. When the sheep lost body mass and were assumed to be in negative energy balance: (1) adipocyte diameter in subcutaneous adipose tissue was smaller and decreased to a greater extent in Tibetan than in Small-tailed Han sheep, but the opposite occurred in the visceral adipose tissue; (2) Tibetan sheep showed higher insulin receptor mRNA expression and lower concentrations of catabolic hormones than Small-tailed Han sheep and (3) Tibetan sheep had lower capacity for glucose and fatty acid uptake than Small-tailed Han sheep. Moreover, Tibetan sheep had lower AMPK α mRNA expression but higher mammalian target of rapamycin mRNA expression in the adipocytes than Small-tailed Han sheep. We concluded that Tibetan sheep had lower catabolism but higher anabolism in adipose tissue and reduced the capacity for glucose and fatty acid uptake to a greater extent than Small-tailed Han sheep to maintain energy homoeostasis when in negative energy balance. These responses provide Tibetan sheep with a high ability to cope with low energy intake and with the harsh environment of the QTP.